2011
DOI: 10.1016/j.jadohealth.2011.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The Decision to Access Patient Information From a Social Media Site: What Would You Do?

Abstract: Purpose The current study examined the prevalence with which healthcare providers use a social media site account (e.g., Facebook), the extent to which they utilize social media sites in clinical practice, and their decision-making process after accessing patient information from a social media site. Methods Pediatric faculty and trainees from a medical school campus were provided a social media site history form and seven fictional social media site adolescent profile vignettes that depicted concerning info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
2
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 14 publications
0
56
2
4
Order By: Relevance
“…17 A study of pediatric faculty and trainees found that 14% to 18% of trainees (but no faculty) had conducted an Internet or social media Web site search for information about a patient; 14% of faculty stated they would conduct an Internet search for additional patient information if necessary. 18 Some physicians also make the deliberate decision to "friend," or connect, on social networks with their patients to engage patients and seem more approachable. 19 Others have done so with less certainty and have reflected on the complexity of the situation.…”
Section: Circulationmentioning
confidence: 99%
See 2 more Smart Citations
“…17 A study of pediatric faculty and trainees found that 14% to 18% of trainees (but no faculty) had conducted an Internet or social media Web site search for information about a patient; 14% of faculty stated they would conduct an Internet search for additional patient information if necessary. 18 Some physicians also make the deliberate decision to "friend," or connect, on social networks with their patients to engage patients and seem more approachable. 19 Others have done so with less certainty and have reflected on the complexity of the situation.…”
Section: Circulationmentioning
confidence: 99%
“…18 However, significant variation exists in how providers would respond to accessed information. For example, when pediatric trainees and faculty were given a series of hypothetical vignettes involving concerning information (eg, suicidal ideation or reference to drug use) gleaned from a patient's public social media site profile, respondents differed on how they would use that information, from immediately contacting the parents/guardians or law enforcement to using that information at the next clinical visit to doing nothing.…”
Section: Looking Up Information About Patients On the Internetmentioning
confidence: 99%
See 1 more Smart Citation
“…Varios autores (Jent et al, 2011;Moorhead et al, 2013;Veneroni et al, 2015) alertan sobre el peligro que entraña este último uso y señalan al mismo tiempo la necesidad de controlar, monitorizar o establecer algún tipo de protocolo que regule la interacción entre médicos y usuarios a través de las redes sociales.…”
Section: Palabras Claveunclassified
“…Por su parte, Jent et al (2011) ahondan en las poten cialidades de esa interacción pero insisten, como hacían los estudios mencionados sobre redes sociales en gene ral, en la necesidad de establecer guías o criterios para articularla. De hecho, una extensión muy frecuente de esta interacción es la creación de grupos de pacientes, familiares cuidadores, profesionales o varios de estos colectivos simultáneamente (Al Mamun, Ibrahim & Turin, 2015;Frimming, Polsgrove & Bower, 2011;Gajaria, Yeung, Goodale & Charach, 2011;Leis et al 2013;Zhang, He & Sang, 2013).…”
Section: Marco Teóricounclassified